Prevalence of Ocular Disorders in Learning Disabled Children and Their Functional Visual Performance Before and After Providing Spectacle Correction - Parikshit Gogate; Jason Raj William; Amit Shinde; Shashi Bhushan (Delhi Journal of Ophthalmology)
Aim: To determine the prevalence of ocular disorders and the functional visual performance in learning disabled children, before and after providing spectacle correction. Method: A prospective, interventional, study was done in five special schools in Pune. A comprehensive ocular examination of children with IQ (Intelligence Quotient) level <70 was done in the mobile eye clinic. Visual acuity was assessed with the help of Cardiff acuity cards. Cycloplegic refraction was performed in all children whose visual acuity was <0.2 Log MAR. Necessary spectacle correction was dispensed to all children with significant uncorrected refractive error. Functional visual performance of the child with refractive error was assessed with the help of modified L.V. Prasad – Functional Vision Questionnaire administered to child’s parents with a set of 10 items and to teachers with a set of 8 items, before and two months after providing spectacles. Statistical analysis was done with SPSS. Wilcoxon sign ranking test was used for the comparison of post vs pre questionnaire scores. Results: Out of 254 children examined, 178 (70.1%) were male. They were aged between 8-18 years. 104 children had mild learning disability (IQ of 50-69), 123 children had moderate (IQ of 35-49), 26 children had severe (IQ of 20-34) and one child had profound learning disability (IQ<20). Only 7(2.8%) children were found to be wearing spectacles at the time of examination. 114 (44.9%) had visual acuity <0.2 Log MAR. 11 children were very uncooperative for refraction and three children had no glow on retinoscopy. Among those 100 children (200eyes) who co-operated for refraction, 77 (38%) eyes were hypermetropic, 64 (32%) eyes had astigmatism, 53 eyes (26.5%) were myopic and six (3%) eyes were found to be emmetropic. 57 children (22.4%) had strabismus, while nystagmus was present in 37 children (14.6%), cataract in three children (1.2%) and retinitis pigmentosa in two children (0.8%) (who were siblings). It was found that improvement in functional visual performance post intervention was significant (p <0.0001) for each question. Conclusions: There was a high prevalence of ocular disorders among learning disabled children. A comprehensive ocular examination, with refraction, followed by spectacle dispensing improved their visual function significantly.